Independent risk factors and the potential predictors of bladder cancer-related ischemic stroke. Issue 4 (April 2020) - Quan, Xuemei; Qin, Qixiong; Chen, Ya; Wei, Yunfei; Xie, Xianlong; Wang, Dacheng; Li, Haihua; Li, Shengyu; Cheng, Daobin; Liang, Zhijian
Objective: To investigate the independent risk factors and potential predictors of bladder cancer-related ischemic stroke (BCRIS). Methods: This was a multi-center retrospective study including patients with active bladder cancer and acute ischemic stroke without traditional stroke risk factors (BCRIS group), and sex- and age-matched patients with active bladder cancer alone (control group). Data were collected between January 2006 and December 2018. Uni- and multivariate analyses were performed to identify independent risk factors for BCRIS. The predictive performance of these risk factors was assessed using receiver operating characteristic (ROC) curves. Results: Records were retrospectively reviewed from 60 BCRIS patients and 120 bladder cancer controls. Univariate analysis revealed that serum D-dimer and carcinoembryonic antigen (CEA) levels and the platelet and neutrophil counts were significantly higher in BCRIS patients compared with controls. Multivariate analysis identified the three above-mentioned variables as independent risk factors for BCRIS. The product of all three factors gave the largest area under the ROC curve. Conclusions: Elevated serum D-dimer and CEA levels and increased platelet count were independent risk factors for BCRIS, and the cut-off value based on the product of the three independent risk factors (≥2, 640, 745.29) could serve as a potential predictor of BCRIS.